Diagnosis and treatment of very large polyps found within the bowel cancer screening programme: experience of practice in a large single screening centre. (13th March 2011) - Neale, J; Patel, P; Snowball, J; Halloran, S
Abstract : Introduction: A high number of polyps are found in the English Bowel Cancer Screening Programme (BCSP). This includes a significant number of large (>1 cm) and very large (>2 cm) polyps. These are challenging to treat. Historically very large polyps have required surgical intervention. However, developing advanced polypectomy/EMR skills allow for the majority to be removed endoscopically by appropriately trained endoscopists. There is currently a lack of data on the outcome of very large polyps found during colonoscopy. Methods: Data for all colonoscopies performed within the Hampshire Bowel Cancer Screening Centre was retrieved from the Bowel Cancer Screening Database at the Southern screening hub covering the period May 2008 to March 2010. This was subanalysed into those with high-risk polyps, all of which had benign histology. The data pertaining to these polyps and their management was reviewed. Results: 125 patients were identified as having high-risk polyps. This covers 579 separate polyps. 38% (220) polyps were large, 15% (86) were very large (VL). The initial management of these polyps is set out in the table 1 below. 100% of very large polyps deferred for later endoscopic therapy/EMR have a sessile/flat morphology (compared to 12% removed at index endoscopy, p<0.00001). 94% of these polyps are located outside the rectum or sigmoid colon (compared to 16% removed at index endoscopy, p<0.00001). They are larger than those removed at index endoscopy, but this does not reach significance (mean size = 27 vs 25 mm, p=0.14). 45% of polyps referred for surgery have a sessile/flat morphology (12% at index, p=0.98). They share a similar distribution with 36% being found outside the rectum and sigmoid colon (16% at index, p=0.91). They are larger than those treated at index endoscopy (mean size 29 vs 25 mm, p=0.06). Conclusion: Referral patterns for EMR/Surgery vary. These decisions differ between endoscopists with different experience, even within a single screening centre. The later endoscopy/EMR group have clear differences to those removed at index endoscopy. The polyps in the surgery group were more likely to be sessile and outside the recto-sigmoid, but this study was unable to detect this to a significant level. Multi-centre research is requested to explore this further. There are likely to be other criteria which cause referral to surgery such as surface morphology not picked up by the BCSP database.